A plant nonenveloped double-stranded RNA virus activates and co-opts BNIP3-mediated mitophagy to promote persistent infection in its insect vector. Issue 2 (1st February 2023) - Liang, Qifu; Wan, Jiajia; Liu, Huan; Jia, Dongsheng; Chen, Qian; Wang, Aiming; Wei, Taiyun
ABSTRACT: Mitophagy that selectively eliminates damaged mitochondria is an essential mitochondrial quality control mechanism. Recently, mitophagy has been shown to be induced in host cells infected by a few animal viruses. Here, we report that southern rice black-streaked dwarf virus (SRBSDV), a plant nonenveloped double-stranded RNA virus, can also trigger mitophagy in its planthopper vector to prevent mitochondria-dependent apoptosis and promote persistent viral propagation. We find that the fibrillar structures constructed by the nonstructural protein P7-1 of SRBSDV directly target mitochondria via interaction with the mitophagy receptor BNIP3 (BCL2 interacting protein 3), and these mitochondria are then sequestered within autophagosomes to form mitophagosomes. Moreover, SRBSDV infection or P7-1 expression alone can promote BNIP3 dimerization on the mitochondria, and induce autophagy via the P7-1-ATG8 interaction. Furthermore, SRBSDV infection stimulates the phosphorylation of AMP-activated protein kinase (AMPK), resulting in BNIP3 phosphorylation via the AMPKα-BNIP3 interaction. Together, P7-1 induces BNIP3-mediated mitophagy by promoting the formation of phosphorylated BNIP3 dimers on the mitochondria. Silencing of ATG8, BNIP3, or AMPKα significantly reduces virus-induced mitophagy and viral propagation in insect vectors. These data suggest that in planthopper, SRBSDV-induced mitophagosomes are modified to accommodate virions and facilitate persistent viral propagation. In summary, our results demonstrate a previously unappreciated role of a viral protein in the induction of BNIP3-mediated mitophagy by bridging autophagosomes and mitochondria and reveal the functional importance of virus-induced mitophagy in maintaining persistent viral infection in insect vectors.Abbreviations: AMPK: AMP-activated protein kinase; ATG: autophagy related; BNIP3: BCL2 interacting protein 3; CASP3: caspase 3; dsRNA: double strand RNA; ER: endoplasmic reticulum; FITC: fluorescein isothiocyanate; FKBP8: FKBP prolyl isomerase 8; FUNDC1: FUN14 domain containing 1; GFP: green fluorescent protein; GST: glutathione S-transferase; padp: post-first access to diseased plants; Phos-tag: Phosphate-binding tag; PINK1: PTEN induced kinase 1; Sf9: Spodoptera frugiperda ; SQSTM1: sequestosome 1; SRBSDV: southern rice black-streaked dwarf virus; STK11/LKB1: serine/threonine kinase 11; TOMM20: translocase of outer mitochondrial membrane 20; RBSDV: rice black-streaked dwarf virus; TUNEL: terminal deoxynucleotidyl dUTP nick end labeling; ULK1: unc-51 like autophagy activating kinase 1; VDAC1: voltage dependent anion channel 1.